P-555 Improved clinical validity of Preimplantation Genetic Testing for Aneuploidy (PGT-A) using a next-generation sequencing workflow for simultaneous detection of aneuploidy, ploidy and common pathogenic microdeletions. (30th June 2022) - Caroselli, S; Figliuzzi, M; Cogo, F; Zambon, P; Favero, F; Anastasi, A; Capodanno, F; Gallinelli, A; Cimadomo, D; Rienzi, L; Ubaldi, F.M; Miravet-Valenciano, J; et al.
Abstract: Study question: Can chromosomal abnormalities beyond aneuploidies (i.e., ploidy and microdeletions, MD) be detected on a single trophectoderm (TE) embryo biopsy using a next-generation sequencing (NGS)-based workflow? Summary answer: This NGS-based integrated approach allows accurate detection of ploidy status and the most common microdeletions from a single TE-biopsy, expanding PGT-A clinical validity and diagnostic capabilities. What is known already: Standard methodologies employed in PGT-A do not determine embryo ploidy status due to the normalization process during copy-number-variation analysis. Transferring embryos with abnormal ploidy variations is expected to result in miscarriage or molar pregnancy. Common pathogenic MD are undetected as they fall below the PGT-A resolution limit (<10Mb). MD are involved in genomic disorders associated with neurodevelopmental disabilities and multiple congenital anomalies. The development of this sequencing strategy can resolve current limitations and add valuable information regarding the genetic constitution of embryos, which is not usually evaluated in PGT and normally requires the use of later-stage invasive prenatal diagnosis. Study design, size, duration: Ploidy determination was validated using 244 embryo samples of known ploidy status (226 diploids, 10 triploids, 8 haploids). We analysed nine common MD syndromes (-4p=Wolf-Hirschhorn, -8q=Langer-Giedion, -1p=1p36 deletion, -22q=DiGeorge, -5p=Cri-du-Chat, -15q=Prader-Willi/Angelman, -11q=Jacobsen, -17p=Smith-Magenis) using 24 positive controls (amniocentesis DNA from MD cases or TE biopsies from autosomal monosomy mimicking MD) and 96 negative controls (healthy newborns). Overall, the dataset included 72 cases of individual chromosomal abnormalities and 576 negative cases across the eight MD regions. Participants/materials, setting, methods: PGT-A products were reamplified and sequenced (IonTorrentS5-ThermoFisher) using a custom AmpliSeq panel targeting 384 regions with at least one Single Nucleotide Polymorphism (SNP) of high B-allelic frequency. A bioinformatic algorithm based on gaussian-mixture modelling of sequencing data was developed. This algorithm calculates the conditional probability of the observed B-allelic ratio for each SNP, depending on the copy number, then estimates the likelihood of ploidy and the presence of MD based on the sequencing outcomes. Main results and the role of chance: Ploidy was correctly determined in 233/234 cases (Accuracy=99.4%), with only one diploid sample misclassified as triploid (PPV=94.1%, NPV=100%, Non-informative rate=9/243=3.1%). Microdeletions could be consistently detected with high reliability in 6 out of the 8 considered regions (-8q, -22q, -5p, -15q, -11q and -17p; PPV=98.5%, NPV=99.5%). Detection of microdeletions of 1p and 4p were less reliable due to the presence of recurrent haplotype blocks in the population at those genomic regions, as confirmed by the analysis of a dataset of 2504 whole genome sequencing from One Thousand Genome Project database (1kGP). The only MD false positive case showed extended loss of heterozygosity in the microdeletion region (-22q), which might be related to uniparental disomy or consanguinity and requires further testing in the family. This analytical framework was blindly applied to: (i) the analysis of 9 embryos from a family affected by DiGeorge syndrome (female partner was carrier of del22.q11.21(20754422-21440514), resulting in all embryos classified consistently with the conventional PGT-M results (using indirect linkage analysis); (ii) the analysis of samples from 99 transferred human euploid embryos resulting in pregnancy losses. No ploidy alteration was detected in miscarried euploid embryos, but 2 microdeletions (-8q, -22q) were found, with an estimated prevalence of 2/99 in the miscarriage population. Limitations, reasons for caution: Larger cohort studies will be required to accurately assess the incidence of ploidy alterations and microdeletions in preimplantation embryos and particularly in euploid miscarriages. Despite the high accuracy of the assay developed, the use of parental DNA to support diagnostic calling can further increase the precision of the assay. Wider implications of the findings: This study provides, for the first time, detection of common pathogenic microdeletions and ploidy status from a single TE biopsy, expanding PGT-A clinical validity. This new assay will also help elucidate fundamental biological and clinical questions related to the genetics of implantation failure and pregnancy loss of apparently euploid embryos. Trial registration number: not applicable